2020
DOI: 10.1016/j.mehy.2020.109773
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19, TMPRSS2, and whether android regulation affects pandemic virus gender incidence and age distribution of disease

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Its expression in the lung and sputum has been found to be higher in men than in women [ 62 , 68 ]. This is consistent with the increased susceptibility of men to COVID-19 because the increased TMPRSS2 allows for increased viral entry [ 64 ]. TMPRSS2 also has an estrogen-responsive promoter, a mechanistic step that may be of significance in the hormonal control in pediatric patients as compared to adults [ 69 ].…”
Section: Mechanistic Considerations In Diagnosis In Childrensupporting
confidence: 75%
See 1 more Smart Citation
“…Its expression in the lung and sputum has been found to be higher in men than in women [ 62 , 68 ]. This is consistent with the increased susceptibility of men to COVID-19 because the increased TMPRSS2 allows for increased viral entry [ 64 ]. TMPRSS2 also has an estrogen-responsive promoter, a mechanistic step that may be of significance in the hormonal control in pediatric patients as compared to adults [ 69 ].…”
Section: Mechanistic Considerations In Diagnosis In Childrensupporting
confidence: 75%
“…TMPRSS2 is essential for entry of a variety of viruses, such as SARS-Cov-2, MERS-Cov, human coronavirus 229E (HCov-229E), influenza A virus, and influenza B virus, in the primary human type II pneumocytes and enhances the virulent effects on the host [ 46 , 62 , 63 ]. Subsequently, there is emerging therapeutic potential of TMPRSS2 inhibitors in the treatment of COVID-19 [ 46 , 64 ]. The TMPRSS2 gene, located on human chromosome 21, has several androgen receptor elements and TMPRSS2 protein is expressed in an androgen-dependent manner both in prostate and lung cancer cells [ 65 , 66 ].…”
Section: Mechanistic Considerations In Diagnosis In Childrenmentioning
confidence: 99%
“…It is reported that the male predominance phenomena of COVID-19 might be due to the androgen-driven pathogen of SARS-CoV‑2 [ 26 ]. In contrast, estrogen can increase the Interferon-gamma (IFN-γ) promoter’s activity, which participates in the responses to viral pathogens [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This loop results in a rapidly progressive and widespread alveolar damage [ 11 ]. Transmembrane Protease, Serine 2 (TMPRSS2) by contrast, is a transmembrane serine protease receptor (required for S protein priming, which may prevent cell entry of SARS-CoV-2 [ 59 ]. A TMPRSS2 inhibitor blocking entry might constitute a treatment option of SARS-CoV-2 [ 60 ].…”
Section: The Mechanism Of Sars-cov-2 Entrymentioning
confidence: 99%